Walter and Miller's textbook of radiotherapy radiation physics, theraphy and oncology - Symonds, Paul; Walter, J. (Joseph) (Elsevier / Churchill Livingstone, 2012)
A comprehensive textbook of radiotherapy and related radiation physics and oncology for use by all those concerned with the uses of radiation and cytotoxic drugs in the treatment of patients with malignant disease. Walter & Miller's Textbook of Radiotherapy has become the core text for therapeutic radiography students and an important introductory text for trainee radiologists and clinical physicists. The book is divided into two parts: the first covers underlying principles of physics, and the second is a systematic review by tumour site concentrating on the role of radiotherapy in the treatment of malignant disease and setting its use in context with chemotherapy and surgery. The 7th edition continues the tradition of bringing the physics and clinical application of radiation for therapy together at entry level and is completely revised to take into account the huge technological advances in radiotherapy treatment since publication of the previous edition.